Evaluation of Compliance with Sharia Principles in Financial Reports (Case Study of Saro Niaga Store, Bone Regency). - Dita Natasya Yahya; Hamzah, Aksi; Muis, Musrini (Journal of Islamic Economic and Business Studies, 2025)
This study aims to instill sharia principles in financial reports, with a case study at Saro Niaga Store in Bone Regency. As one of the major business actors in the staple food retail sector, Saro Niaga Store is expected to be able to comply with sharia principles such as the prohibition of usury, gharar, and maysir in its financial reporting. This study uses a qualitative approach with a descriptive method through interviews, observations, and document analysis. The results of the study indicate that the application of sharia principles at Saro Niaga Store still faces obstacles such as limited understanding of sharia accounting standards and challenges in the consistency of its implementation. However, there are efforts to improve compliance, including the implementation of a computer-based reporting system that supports transparency and accountability. This study suggests strategic steps to improve understanding and compliance with sharia principles, which not only impact the company's reputation but also strengthen Muslim consumer confidence.